Men of Valor : Thin Ice - Book 2 - Hannon, Irene (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2016)
"FBI Special Agent Lance McGregor, a former Delta Force operator, is assigned to the case when Christy Reed receives mail claiming her sister is still alive. She believed Ginny died in a house fire, so if she is still alive, who is the woman buried in her grave and is Christy a pawn or a target?"--
Keywords: Women police chiefs -- Fiction; Murder -- Fiction -- Investigation; Mystery fiction; Christian fiction